Nanostructures for Enhanced Light Absorption in Solar Energy Devices. (15th June 2011) - Edman Jonsson, Gustav; Fredriksson, Hans; Sellappan, Raja; Chakarov, Dinko
Abstract : The fascinating optical properties of nanostructured materials find important applications in a number of solar energy utilization schemes and devices. Nanotechnology provides methods for fabrication and use of structures and systems with size corresponding to the wavelength of visible light. This opens a wealth of possibilities to explore the new, often of resonance character, phenomena observed when the object size and the electromagnetic field periodicity (light wavelength λ ) match. Here we briefly review the effects and concepts of enhanced light absorption in nanostructures and illustrate them with specific examples from recent literature and from our studies. These include enhanced optical absorption of composite photocatalytically active TiO2 /graphitic carbon films, systems with enhanced surface plasmon resonance, field-enhanced absorption in nanofabricated carbon structures with geometrical optical resonances and excitation of waveguiding modes in supported nanoparticle assembles. The case of Ag particles plasmon-mediated chemistry of NO on graphite surface is highlighted to illustrate the principle of plasmon-electron coupling in adsorbate systems.